2012
DOI: 10.1038/leu.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia-related chromosomal loss detected in hematopoietic progenitor cells of benzene-exposed workers

Abstract: Benzene exposure causes acute myeloid leukemia, and hematotoxicity, shown as suppression of mature blood and myeloid progenitor cell numbers. As the leukemia-related aneuploidies monosomy 7 and trisomy 8 previously had been detected in the mature peripheral blood cells of exposed workers, we hypothesized that benzene could cause leukemia through the induction of these aneuploidies in hematopoietic stem and progenitor cells. We measured loss and gain of chromosomes 7 and 8 by fluorescence in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…However, benzene is considered the main carcinogenic agent (group 1 according to IARC) and studies associate this compound with acquired cytogenetic alterations [57]. Among various forms of benzene-induced genetic alterations, aneuploidy and chromosomal breakage are the most studied [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, benzene is considered the main carcinogenic agent (group 1 according to IARC) and studies associate this compound with acquired cytogenetic alterations [57]. Among various forms of benzene-induced genetic alterations, aneuploidy and chromosomal breakage are the most studied [4].…”
Section: Discussionmentioning
confidence: 99%
“…Among various forms of benzene-induced genetic alterations, aneuploidy and chromosomal breakage are the most studied [4]. Chromosomal aberrations in peripheral blood lymphocytes of chronically benzene-exposed patients were previously documented [57]. Zhang et al [5] reported dose-dependent chromosomal aneuploidies (mono- and trisomies) in the peripheral blood lymphocytes of workers exposed to benzene.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2011) has reported dose-dependent chromosomal aneuploidies (monosomy & trisomy) in the peripheral blood lymphocytes of 47 workers exposed to benzene . In another study published by Zhang et al (2012) an increased monosomy 7 and 8 level was found in 28 benzene-exposed workers in comparison to control subjects . Macron et al…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Recent investigations continue to assess and report the frequent detection of increased chromosomal aberrations among benzene exposed leukemia patients (Paz-y-Mino et al 2008;Kim et al 2010;Zhang et al 2011;Ji and Zhang 2012;Zhang et al 2012). For additional studies and investigations on the cytogenetic effects of benzene, please see Kim et al (2004), Holeckova et al (2004), Zhang et al (2002), Marcon et al (1999), Smith et al (1998), Zhang et al (1996), Ciccone et al (1993), Katz et al (1992), Shannon et al (1992), Cuneo et al (1992), Robertson et al (1991), Garson (1984), Rowley (1983) and Mitelman et al (1981).…”
Section: Molecular Epidemiologymentioning
confidence: 99%